2020
DOI: 10.1007/s10143-020-01429-6
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation electrodes may rotate after implantation—an animal study

Abstract: Directional deep brain stimulation (dDBS) electrodes allow to steer the electrical field in a specific direction. When implanted with torque, they may rotate for a certain time after implantation. The aim of this study was to evaluate whether and to which degree leads rotate in the first 24 h after implantation using a sheep brain model. dDBS electrodes were implanted in 14 sheep heads and 3D rotational fluoroscopy (3D-RF) scans were acquired to visualize the orientation of the electrode leads. Electrode leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…These results showed as hypothesized by the investigators that independent from biological factors such as brain shift, mechanical manipulation could have a substantial effect on electrode rotation. In addition, neither time course nor the degree of rotation seemed to be predictable [13].…”
Section: Discussion/ Conclusionmentioning
confidence: 94%
See 1 more Smart Citation
“…These results showed as hypothesized by the investigators that independent from biological factors such as brain shift, mechanical manipulation could have a substantial effect on electrode rotation. In addition, neither time course nor the degree of rotation seemed to be predictable [13].…”
Section: Discussion/ Conclusionmentioning
confidence: 94%
“…In addition, depending on the imaging modality and/or the access angle of the lead determination of the rotational angle might be prone to errors [20]. Importantly, one in vivo study suggested that simple mechanical manipulation of the electrode during surgery might be responsible for electrode rotation [13].…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of our analysis is that the postoperative CT scans and the intraoperative X-rays used for visual confirmation of the correct solution were not performed at the same time. As shown in an animal study [ 9 ], DBS leads may rotate during the first 24 h after implantation if torque is present. However, these changes are not expected to exceed 60° and thus are not likely to have impacted our analysis regarding the 180° ambiguity of the marker artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…This selection process can be guided by a priori neuroanatomical knowledge [ 3 ], probabilistic sweet spots [ 4 , 5 ] or individual neuroimaging [ 6 ], but detailed information about the lead’s location and orientation with respect to the surrounding anatomy is needed. Previous results showed that the precise placement of a directional lead into the desired orientation is difficult due to lead torsion [ 7 ], which additionally can lead to changes in a lead’s orientation within the first days after implantation [ 8 , 9 , 10 ]. Consecutively, lead orientation needs to be derived from postoperative imaging, and different methods have been proposed for different imaging techniques [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the need for translational lead stability relative to an anatomic target for effective DBS has been widely appreciated, [4][5][6][7][8][9][10][11] the advent of directional electrodes highlights a new need for rotational stability. [12][13][14][15] Dembek et al 12 recently found a wide range of angular deviations for 198 leads in 100 patients when they compared rotational lead orientations at implant and postoperatively in a segmented electrode lead from one manufacturer. The researchers found that 41% of the leads studied had deviations of 30 • or greater when using bone cement and a microplate to stabilize the leads.…”
Section: Introductionmentioning
confidence: 99%